Convergence of decreasing male and increasing female incidence rates in major tobacco-related cancers in Europe in 1988–2010. Issue 9 (June 2015) - Lortet-Tieulent, Joannie; Renteria, Elisenda; Sharp, Linda; Weiderpass, Elisabete; Comber, Harry; Baas, Paul; Bray, Freddie; Coebergh, Jan Willem; Soerjomataram, Isabelle
Abstract Introduction Smoking prevalence has been declining in men all over Europe, while the trend varies in European regions among women. To study the impact of past smoking prevalence, we present a comprehensive overview of the most recent trends in incidence, during 1988–2010, in 26 countries, of four of the major cancers in the respiratory and upper gastro-intestinal tract associated with tobacco smoking. Methods Data from 47 population-based cancer registries for lung, laryngeal, oral cavity and pharyngeal, and oesophageal cancer cases were obtained from the newly developed data repository within the European Cancer Observatory (http://eco.iarc.fr/). Truncated age-standardised incidence rates (35–74 years) by calendar year, average annual percentage change in incidence over 1998–2007 were calculated. Smoking prevalence in selected countries was extracted from the Organisation for Economic Co-operation and Development and the World Health Organization databases. Results There remained great but changing variation in the incidence rates of tobacco-related cancers by European region. Generally, the high rates among men have been declining, while the lower rates among women are increasing, resulting in convergence of the rates. Female lung cancer rates were above male rates in Denmark, Iceland and Sweden (35–64 years). In lung and laryngeal cancers, where smoking is the main risk factor, rates were highest in central and eastern Europe, southern Europe and the Baltic countries. Despite a lowering of female smoking prevalence, female incidence rates of lung, laryngeal and oral cavity cancers increased in most parts of Europe, but were stable in the Baltic countries. Mixed trends emerged in oesophageal cancer, probably explained by differing risk factors for the two main histological subtypes. Conclusions This data repository offers the opportunity to show the variety of incidence trends by sex among European countries. The diverse patterns of trends reflect varied exposure to risk factors. Given the heavy cancer burden attributed to tobacco and the fact that tobacco use is entirely preventable, tobacco control remains a top priority in Europe. Prevention efforts should be intensified in central and eastern Europe, southern Europe and the Baltic countries.